2021
DOI: 10.1039/d1bm00112d
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin nanoparticles boost abscopal effect of radiation plus anti-PD1 therapy

Abstract: The abscopal effect of radiation therapy (RT) is clinically significant but occurs rarely. Although anti-programmed cell death protein 1 antibody (anti-PD1) is likely to enhance the abscopal effect in patients...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“… 423 Of note, Wang et al reported that cisplatin nanoparticles can promote the abscopal effect induced by RT with PD1 inhibitors which breaks through the efficiency limitation of iRT. 424 …”
Section: Clinical Practicementioning
confidence: 99%
“… 423 Of note, Wang et al reported that cisplatin nanoparticles can promote the abscopal effect induced by RT with PD1 inhibitors which breaks through the efficiency limitation of iRT. 424 …”
Section: Clinical Practicementioning
confidence: 99%
“…First, we selected doses of 7 mg/kg for CDDP and 15 mg/kg for CDDP-NPs (eq to CDDP) as they have similar toxicity . Second, since CDDP-NPs have prolonged blood circulation, greater accumulation, and more Pt-DNA adducts , in a tumor at 72 h, the superior host immune response would probably last for a prolonged duration. Thus, 72 h was selected as the appropriate time point to investigate the superior host immune response of CDDP-NPs compared to CDDP.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the enhanced immune response and abscopal effects. [ 253 ] Additionally, the srNPs synergistic immunotherapy for training immune cells can produce specific antibodies to establish immune memory to inhibit the recurrence of cancer in the cradle. [ 254 ] Notably, m‐srNPs responsive to external and internal stimuli are more effective and intelligent in regulating drug release than single responsive systems.…”
Section: Discussionmentioning
confidence: 99%